Upaya Meningkatkan Kemampuan Guru IPA dalam Mendesain Pembelajaran Berbasis Kearifan dan Potensi Lokal - Sriyati, Siti; Liliawati, Winny; Yuliani, Galuh (Penerbit Goodwood, 2023)
Purpose: Carry out training to improve the ability of science teachers to design teaching materials based on local wisdom and local potential. Methodology/approach: Community Service activities are carried out 3 times (2 online meetings and 1 offline meeting) with a lesson study pattern (planning, doing, seeing). There are around 50 science teachers in online activities from all over Indonesia, while offline activities are carried out for science teachers in Cirebon and surrounding areas. Result: The results of community service activities are 1). Produced several teaching materials based on local wisdom and local potential from various regions where participants come from, 2). Positive responses from science teachers about learning based on local wisdom and local potential, 3). From the open lesson activity, the Observer teacher stated that the learning was carried out very well (100%). 4). From reflection activities, teachers see that students learn enthusiastically and teachers learn about making and implementing learning based on local wisdom and potential. Limitation: The local potential-based learning chosen by the teacher is the biotechnology concept of Cirebon Bakung tape and Kuningan tape. The instruments used are teacher questionnaires and observation sheets. Contribution: Community service activities can provide insight for teachers to create and implement learning based on local wisdom and local potential